Processing of the Ti25Ta25Nb3Sn Experimental Alloy Using ECAP Process for Biomedical Applications - Bortolini, Celso [UNESP]; Carobolante, João Pedro Aquiles [UNESP]; Timokhina, Ilana; Caporalli Filho, Angelo [UNESP]; Rosifini Alves, Ana Paula [UNESP] (MDPI, 2023)
The development of titanium-β alloys for biomedical applications is associated with the addition of alloying elements or the use of processing techniques to obtain suitable bulk properties. The Ti25Ta25Nb3Sn alloy has been highlighted for its mechanical properties and biocompatibility. To further enhance the properties of titanium alloys for biomedical applications, equal channel angular pressing (ECAP) was used due to its capability of refining the microstructure of the alloy, leading to improved mechanical properties without significant changes in Young’s modulus. This study aims to evaluate the impact of ECAP on the microstructure of the Ti-25Sn-25Nb-3Nb alloy and investigate the correlation between the microstructure, mechanical properties, and corrosive behavior. Grain refinement was achieved after four ECAP passes, with an average grain diameter of 395 nm and a non-homogeneous structure, and microhardness was slightly increased from 193 to 212 HV after four ECAP passes. The thermomechanical aspects of the ECAP processing have led to the formation of a metastable α″ phase during the first two passes, while after four passes, the structure was composed only of the β phase. The corrosion resistance of the alloy was increased after four passes, presenting the best results in terms of the improvement of passivation corrosion density.
Keywords: biomaterials; ECAP; mechanical processing; titanium alloys